Recent Advances on Rare Earth Upconversion Nanomaterials for Combined Tumor Near-Infrared Photoimmunotherapy - Chen, Weilin; Xie, Yulin; Wang, Man; Li, Chunxia (Frontiers in Chemistry, 2020)
Cancer has been threatening the safety of human life. In order to treat cancer, many methods have been developed to treat tumor, such as traditional therapies like surgery, chemotherapy, radiotherapy, as well as new strategies like photodynamic therapy, photothermal therapy, sonodynamic therapy and other emerging therapies. Although there are so many ways to treat tumors, these methods all face the dilemma that they are incapable to cope with metastasis and recurrence of tumors. The emergence of immunotherapy has given the hope to conquer the challenge. Immunotherapy is to use the body’s own immune system to stimulate and maintain a systemic immune response to form immunological memory, resist the metastasis and recurrence of tumors. At the same time, immunotherapy can combine with other treatments to exhibit excellent antitumor effects. Upconversion nanoparticles (UCNPs) can convert near-infrared (NIR) light into ultraviolet and visible light, thus have good performance in bioimaging and NIR triggered phototherapy. In this review paper, we summarize the design, fabrication and application of UCNPs-based NIR photoimmunotherapy for combined cancer treatment, as well as put forward the prospect of future development.